Evaluation of Ground Vibration Induced by Blasting During the Excavation of a Transportation Tunnel in Istanbul Metropolis - Umit Ozer; Ali Kahriman; Mehmet Aksoy; Abdulkadir Karadogan; Deniz Adiquzel; Suat Bicer (International Society of Explosives Engineers, 2008)
This paper presents the analysis and measurements of blast-induced ground vibrations during the construction of Istanbul Kagithane – Piyalepasa – Dolapdere – Dolmabahçe highway tunnels. These tunnels known as T1 and T2 are being constructed by a joint venture group. Within the scope of the study, the particle velocities and frequencies associated with 126 shots during the advancement of the tunnels were monitored and analyzed by vibration monitors at the test site. During the statistical analysis, three different predictor equations widely used in the literature were used to predict peak particle velocity (PPV) and the results and comparison of the predictor equations are presented in this paper. Finally, the particle velocities and frequency values of all blast events were evaluated according to USBM and German DIN 4150 Norms in order to determine the damage risks of the neighboring buildings and structures.